A series of perovskite materials for oxidative coupling of methane to produce ethane and ethylene and preparation methods thereof
By using perovskite material catalysts, the problems of poor stability and low C2 selectivity of methane oxidation coupling catalysts in the prior art are solved, and the catalytic effect of high stability and high C2 selectivity is achieved, meeting the needs of industrial applications.
Patent Information
- Application Number
- CN202111494008.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-12-08
AI Technical Summary
The existing methane oxidation coupling catalysts have poor stability and low C2 selectivity during long-term use, which cannot meet the requirements of industrial applications.
The perovskite material catalyst is used, specifically BaMO3-δ or BaM1-xYxO3-δ, where M is Zr or Ce and x is 0.1-0.2, and is synthesized by the sol-gel method, with alkali metals, diverse surfactant oxygen species, proton conductivity and oxygen ion conductivity.
It significantly improves the stability and C2 selectivity of the catalyst, can run for a long time at high temperatures, solves the problem of carbon deposits, and achieves efficient methane conversion and preparation of ethylene and ethane.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic reactions, and in particular relates to a series of perovskite materials for preparing ethane and ethylene through oxidative coupling of methane and a preparation method thereof. Background Art
[0002] Methane is the main component of natural gas, biogas and petroleum gas. It is an important fuel and chemical raw material (it is the raw material for synthetic ammonia, synthetic methanol, gasoline and other industries). Its chemical conversion pathways can be divided into two categories: one is the indirect conversion method: first, methane is converted into a stable intermediate (such as HCN, CO+H 2 , CH 3 OH, CS 2 ) and then convert it into high-carbon hydrocarbons or chemical raw materials. The other type is the direct conversion method: that is, methane is directly converted into chemical raw materials such as ethane and ethylene in one step. The indirect conversion method of methane based on synthesis gas has been widely studied, and the industrial process of synthesizing ammonia, synthesizing methanol and synthesizing gasoline from methanol has been realized. However, there is no industrial process for the direct conversion of methane. Through the direct conversion method, important chemical raw materials ethylene and ethane can be obtained in one step. Therefore, this process has potential huge economic benefits and has received widespread attention at home and abroad. It is generally believed that the methane oxidative coupling reaction can only compete with the C2 produced by petroleum cracking when the C2 yield reaches 30% and the selectivity is above 65%. However, the catalyst system currently developed has two major challenges for the catalyst: key issues such as catalyst selectivity and stability. At present, it is reported that the highest C2 yield is about 25%, but the catalyst is easily deactivated and cannot meet the requirements of industrialization. Therefore, it is urgent to develop a new catalyst system with high stability.
[0003] The existing catalysts for methane oxidative coupling are mainly divided into three types: Li / MgO system, in which the active center is generally believed to be Li + O - , Li loss occurs during long-term operation, and poor stability is the key factor limiting its practical use as an OCM catalyst; Mn / Na 2 WO 4 / SiO 2 Some studies believe that the active center is Na-O-Mn, while other studies believe that the active center is W=O and WO-Si. Due to the complexity of the structure and chemistry and the difficulty in defining the active center, it is difficult to clearly study the specific reaction mechanism. In addition, La 2 O 3 Based on the system, strong alkaline sites can be generated by doping alkaline earth metals (Sr, Mg, Ca), and the stable operation time reported in the literature is 48h. Therefore, it is of great significance to develop a new catalyst system with high stability.
[0004] Since the main by-products of the methane oxidative coupling reaction are CO and CO 2 , the catalyst also has the problem of carbon deposition, so new catalysts are mainly developed to address these two major problems. Since the essential requirement of the catalyst for methane oxidative coupling is to have a suitable number and strength of basic sites, if the basic sites on the catalyst are too strong, it is easier to react with CO 2 Combined with CO, the active center is occupied to form stable carbonates and lose the catalytic effect, so the newly developed catalyst is required to have excellent CO resistance. 2 The newly developed catalyst has the ability to remove acidic gases such as carbon dioxide, and the catalyst surface has a suitable number and strength of basic sites. In addition, because the newly developed catalyst has proton, electron and oxygen ion conductivity, it can help to convert carbon deposits in a timely manner to a certain extent, thereby successfully solving the carbon deposit problem. Summary of the invention
[0005] In the fixed-bed methane oxidative coupling process to olefins, the size of the catalyst, the ratio of methane to oxygen, and the reaction space velocity all affect the performance of methane coupling. Perovskite materials have excellent stability under methane oxidative coupling conditions, and improving the stability of the catalyst and C2 selectivity is the key to achieving industrial application.
[0006] The purpose of the present invention is to solve the problems of poor long-term stability and low C2 selectivity of existing catalysts in the methane coupling to olefin system, and to propose a series of perovskite catalysts with ingenious structures and long-term stability for the preparation of C2 high value-added chemicals.
[0007] The present invention provides a series of perovskite material catalysts for the oxidative coupling of methane to ethane and ethylene, wherein the perovskite material catalyst is BaMO 3-δ or BaM 1-x Y x O 3-δ , wherein M is Zr or Ce, x is 0.1-0.2, and δ represents non-stoichiometric oxygen; the perovskite material catalyst contains an alkali metal, which can provide a reaction site with moderate alkalinity; the perovskite material catalyst has a variety of surface active oxygen species; the perovskite material catalyst has both proton conductivity and electronic conductivity, and oxygen ion conductivity;.
[0008] Based on the above technical solution, preferably, the perovskite material catalyst can be synthesized by a sol-gel method.
[0009] Based on the above technical solution, preferably, the
[0010] The size of the perovskite catalyst varies in the following range: 50-200nm, and the specific surface area varies in the following range: 3.0-10.0m 2 g -1 .
[0011] The present invention also provides a method for preparing the above-mentioned perovskite material catalyst, comprising the following steps:
[0012] Sol-gel method
[0013] (1) weighing the required amount of metal nitrates in sequence, fully dissolving them in deionized water, and stirring until a clear solution is obtained to obtain a nitrate solution;
[0014] (2) Weighing EDTA and citric acid in a molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1; adding citric acid to the above nitrate solution to obtain a clear solution, then adding EDTA, the solution will become a suspension, and then adding ammonia water to adjust the pH value to 8-10, and the solution becomes clear;
[0015] (3) The above solution is continuously heated and stirred until it becomes a sol, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites and most of the organic matter is burned to obtain a primary powder
[0016] (4) transferring the primary powder to a muffle furnace and calcining it in static air to obtain a perovskite material catalyst powder;
[0017] (5) Pressing and sieving the above-mentioned perovskite catalyst powder in a stainless steel mold of a certain size to obtain catalyst particles of a fixed size.
[0018] Based on the above technical solution, preferably, the calcination temperature in step (4) is 600-1000° C. and the calcination time is 3-10 h.
[0019] Based on the above technical solution, preferably, the catalyst particles in step (5) are 20-40 meshes.
[0020] The present invention also provides an application of the above-mentioned perovskite material catalyst, and the perovskite material catalyst can be used for the oxidative coupling of methane to produce ethane and ethylene.
[0021] Beneficial Effects
[0022] (1) Perovskite BaMO of the present invention 3-δ and BaM 1-x Y x O 3-δ(M=Zr or Ce) catalyst overcomes the key problems of the complex preparation method of the traditional methane oxidative coupling catalyst to ethane ethylene and the poor stability of the catalyst. The present invention combines the excellent high temperature stability of the perovskite material and fixes the Ba element at the A position to provide a reaction site with moderate alkalinity; at the same time, this type of perovskite material has a variety of surface active oxygen species, which greatly increases the C2 selectivity. By rationally designing the doping ratio, the stability of the catalyst under reaction conditions can be significantly improved.
[0023] (2) The perovskite material of the present invention, the B-site metal is Zr, Ce, etc. This type of perovskite material can simultaneously have proton, electron, and oxygen ion conductivity under a certain temperature and oxygen partial pressure, so it can help to timely transform carbon deposits to a certain extent, thereby successfully solving the carbon deposit problem.
[0024] (3) The perovskite material of the present invention can generate oxygen vacancies after being doped with the Y element. At the same time, it can provide a rich variety of surface oxygen active species under the reaction conditions, and oxygen active species that are beneficial to the oxidative coupling of methane to ethane and ethylene appear, thereby greatly increasing the C2 selectivity.
[0025] (4) The present invention can design and prepare a perovskite material catalyst with high C2 selectivity, excellent stability and resistance to carbon deposition. The method is simple to synthesize, convenient to operate and low in cost, and can solve the problem of poor stability of existing methane coupling catalysts for ethane and ethylene. At the same time, the prepared catalyst has considerable C2 selectivity, methane conversion rate and excellent stability. DETAILED DESCRIPTION
[0026] The present invention will be further described in the following examples, but the present invention is not limited thereto.
[0027] Example 1
[0028] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, the solution will become a suspension, and then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZrO 3-δ . BaZrO 3-δ The catalyst powder was pre-calcined at 600℃ in static air for 10h, and the catalyst particles of 20-40 mesh were obtained by tableting and sieving. 3-δThe catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under the test conditions, the methane conversion rate is between 25-27%; the C2 selectivity is between 27-30%.
[0029] Example 2
[0030] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, the solution will become a suspension, and then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZrO 3-δ . BaZrO 3-δ The catalyst powder was pre-calcined at 800℃ in static air for 5h, and the catalyst particles of 20-40 mesh were obtained by tableting and sieving. 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under the test conditions, the methane conversion rate is between 28-30%; the C2 selectivity is between 28-30%.
[0031] Example 3
[0032] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, the solution will become a suspension, and then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZrO3-δ . BaZrO 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles of 20-40 mesh were obtained by tableting and sieving. 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under the test conditions, the methane conversion rate is between 27-30%; the C2 selectivity is between 28-32%.
[0033] Example 4
[0034] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZr 0.9 Y 0.1 O 3-δ . 0.9 Y 0.1 O 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles with a size of 20-40 mesh were obtained by tableting and sieving. 0.9 Y 0.1 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under this test condition, the methane conversion rate is between 30-32%; the C2 selectivity is between 35-40%.
[0035] Example 5
[0036] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZr 0.8 Y 0.2 O 3-δ . 0.8 Y 0.2 O 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles with a size of 20-40 mesh were obtained by tableting and sieving. 0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under this test condition, the methane conversion rate is between 30-35%; the C2 selectivity is between 40-45%.
[0037] Example 6
[0038] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, the solution will become a suspension, and then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaCeO 3-δ . BaCeO 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles of 20-40 mesh were obtained by tableting and sieving. 3-δThe catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under the test conditions, the methane conversion rate is between 26-30%; the C2 selectivity is between 35-40%.
[0039] Example 7
[0040] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaCe 0.9 Y 0.1 O 3-δ . Will BaCe 0.9 Y 0.1 O 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles with a size of 20-40 mesh were obtained by tableting and sieving. 0.9 Y 0.1 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under the test conditions, the methane conversion rate is between 30-35%; the C2 selectivity is between 45-48%.
[0041] Example 8
[0042] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaCe 0.8 Y 0.2 O 3-δ . Will BaCe 0.8 Y 0.2 O 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles with a size of 20-40 mesh were obtained by tableting and sieving. 0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 30 mL / min CH 4 +120mL / min He +10mL / min O 2 (CH 4 / O 2 =3 / 1). Under the test conditions, the methane conversion rate is between 28-35%; the C2 selectivity is between 50-55%.
[0043] Example 9
[0044] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZr 0.8 Y 0.2 O 3-δ . 0.8 Y 0.2 O 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles with a size of 20-40 mesh were obtained by tableting and sieving.0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 50 mL / min CH 4 +200mL / min He +10mL / min O 2 (CH 4 / O 2 =5 / 1). Under this test condition, the methane conversion rate is between 25-30%; the C2 selectivity is between 52-61%.
[0045] Example 10
[0046] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaZr 0.8 Y 0.2 O 3-δ . 0.8 Y 0.2 O 3-δ , pre-calculated at 1000℃ for 3h in static air, and the obtained catalyst powder was screened by tableting to obtain catalyst particles of 20-40 mesh. 0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 80 mL / min CH 4 +240mL / min He +10mL / min O 2 (CH 4 / O 2 =8 / 1). Under the test conditions, the methane conversion rate is between 18-20%; the C2 selectivity is between 63-68%.
[0047] Embodiment 11
[0048] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaCe 0.8 Y 0.2 O 3-δ . Will BaCe 0.8 Y 0.2 O 3-δ , pre-calculated at 1000℃ for 3h in static air, and the obtained catalyst powder was screened by tableting to obtain catalyst particles of 20-40 mesh. Weigh 1.0gBaCe 0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 50 mL / min CH 4 +200mL / min He +10mL / min O 2 (CH 4 / O 2 =5 / 1). Under this test condition, the methane conversion rate is between 22-28%; the C2 selectivity is between 59-65%.
[0049] Example 12
[0050] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaCe 0.8 Y 0.2 O 3-δ . Will BaCe 0.8 Y 0.2 O 3-δ , pre-calculated at 1000℃ for 3h in static air, and the obtained catalyst powder was screened by tableting to obtain catalyst particles of 20-40 mesh. Weigh 1.0gBaCe0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was conducted at 750-850°C with a reaction gas of 50 mL / min CH 4 +200mL / min He +10mL / min O 2 (CH 4 / O 2 =8 / 1). Under the test conditions, the methane conversion rate is between 16-23%; the C2 selectivity is between 68-72%.
[0051] Embodiment 13
[0052] According to the technical scheme of the present invention, the required amount of metal nitrate is weighed in sequence, fully dissolved in deionized water, and stirred to a clear solution. Then EDTA and citric acid are weighed according to the molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1. Citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, EDTA does not dissolve, and the solution will become a suspension. Then ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear. The above solution is continuously heated and stirred until it is in a sol state, transferred to an evaporating dish, and roasted on an electric furnace until the mixture spontaneously ignites, and most of the organic matter is burned to obtain the primary powder BaCe 0.8 Y 0.2 O 3-δ . Will BaCe 0.8 Y 0.2 O 3-δ The catalyst powder was pre-calcined at 1000℃ in static air for 3h, and the catalyst particles with a size of 20-40 mesh were obtained by tableting and sieving. 0.8 Y 0.2 O 3-δ The catalyst was placed in a quartz tube for fixed bed testing of methane oxidative coupling. The test was carried out at 800 °C with a reaction gas of 50 mL / min CH 4 +200mL / min He +10mL / min O 2 (CH 4 / O 2 =8 / 1). Under this test condition, the methane conversion rate is about 16%; the C2 selectivity is about 72%, and the catalyst can operate stably for 200h.
[0053] Many embodiments can be cited above. A large amount of experimental data from the applicant proves that, as long as it is within the scope of the technical solution of the present invention, high-performance perovskite catalysts can be successfully prepared for the oxidative coupling of methane to produce ethane and ethylene.
Claims
1. Application of a series of perovskite material catalysts, characterized in that: The perovskite material catalyst is BaM 1- x Y x O 3-δ , wherein M is Zr or Ce, x is 0.1-0.2, and δ represents non-stoichiometric oxygen; The preparation method of the perovskite material catalyst comprises the following steps: (1) weighing the required amount of metal nitrates in sequence, fully dissolving them in deionized water, and stirring until a clear solution is obtained to obtain a nitrate solution; (2) EDTA and citric acid are weighed according to a molar ratio of EDTA: citric acid: total metal ions of 1:1.5:1, and citric acid is added to the above nitrate solution to obtain a clear solution. Then EDTA is added, and the solution becomes a suspension. Then, ammonia water is added to adjust the pH value to 8-10, and the solution becomes clear; (3) Continuously heating and stirring the above solution until it becomes a sol, transferring it to an evaporating dish, and roasting it on an electric furnace until the mixture spontaneously ignites to obtain a primary powder; (4) transferring the primary powder to a muffle furnace and calcining in static air to obtain a perovskite phase catalyst powder; (5) pressing and sieving the above-mentioned perovskite phase catalyst powder in a mold to obtain catalyst particles; The perovskite material catalyst is used for oxidative coupling of methane to produce ethane and ethylene.
2. The use according to claim 1, characterized in that: The calcination temperature in step (4) is 600-1000° C. and the calcination time is 3-10 hours.
3. The use according to claim 1, characterized in that: The catalyst particles in step (5) are 20-40 meshes.
Citation Information
Patent Citations
Methanol self-heating recapitalization perovskite honeycomb ceramic integral catalyzer and method for preparing the same
CN101112684A
Method for preparing yttrium-doped yttrium zirconate proton conductor material under high temperature and high pressure
CN109400151A